Levodopa and pramipexole combination therapy efficacy in Vietnamese patients with Parkinson’s disease: a randomized controlled trial - Minh Van Le; Dat Tien Diep; Tam Thai Thanh Tran; Tho Kieu Anh Pham; Bao Lam Thai Tran; Thang Nguyen (Russian Open Medical Journal)
Early diagnosis and appropriate treatment of Parkinson's disease to minimize the adverse effects of the disease and drug side effects on the patient. Using levodopa combined with pramipexole is an effective therapy for treating Parkinson's disease. Objectives — This study aims to evaluate the treatment outcome of combination therapy with levodopa and pramipexole compared to levodopa monotherapy in Vietnamese Parkinson's patients. Material and Methods — A randomized controlled clinical trial with a 1:1 randomized ratio of 80 individuals with Parkinson's disease. The intervention group received a combination therapy with levodopa/benserazide and pramipexole, and the control group received a monotherapy with levodopa/benserazide. Motor symptoms, non-motor symptoms, The Unified Parkinson's Disease Rating (UPDRS), and The Parkinson's Disease Questionnaire (PDQ-39) scores were assessed before, after, and a follow-up period of 1 and 4 weeks after discharge to evaluate the treatment outcome. Results — Combining therapy with levodopa and pramipexole led to statistically significant improvements in UPDRS and PDQ-39 scores (p<0.05). The mean difference in UPDRS parts I, II, and III after 4 weeks of discharge was -0.5 (p=0.014), -1.68 (p=0.005), and -2.52 (p=0.010) respectively. The quality of life was also enhanced by combining therapy due to a better reduction of PDQ-39 score: 26.0±6.3 versus 32.7±6.4 (p<0.001). The most common side effects were headache, nausea/vomiting, and somnolence. Conclusions — Treatment with levodopa combined with pramipexole improves clinical symptoms and quality of life in patients with Parkinson's, as evidenced by improvements in UPDRS and PDQ-39 scores.